Cold Plasma Irradiation Attenuates Atopic Dermatitis via Enhancing HIF-1α-Induced MANF Transcription Expression - Sun, Tao; Zhang, Xinru; Hou, Chao; Yu, Shujun; Zhang, Yujing; Yu, Zhuo; Kong, Ling; Liu, Changqing; Feng, Lijie; Wang, Dong; Ni, Guohua (Frontiers in Immunology, 2022)
Cold atmospheric plasma has been widely applied in medical treatment clinically, especially skin diseases. However, the mechanism of cold atmospheric plasma on the treatment of skin diseases is still undefined. In this study, dinitrofluorobenzene-induced atopic dermatitis mice model was constructed. Cold atmospheric plasma was able to decrease skin cells apoptosis, relieve skin inflammation, ER stress and oxidative stress caused by dinitrofluorobenzene stimulation, which was mediated by cold atmospheric plasma-induced MANF expression. In terms of mechanism, hypoxia-inducible factor-1α expression was increased intracellularly after cold atmospheric plasma treatment, which further bound to the promoter region of manf gene and enhanced MANF transcriptional expression. This study reveals that cold atmospheric plasma has a positive effect on atopic dermatitis treatment, also demonstrates the regulatory mechanism of cold atmospheric plasma on MANF expression via HIF-1α, which indicates the potential medical application of cold atmospheric plasma for atopic dermatitis treatment.